Seroprevalencia de anticuerpos sars-cov-2 e higiene de manos en internos de medicina y enfermería de la Universidad Nacional de Loja - Cumbicus Mejía, Andrea Michelle (2022)
COVID-19, a viral respiratory disease generated by SARS-CoV-2, with a high contagion capacity, generating a pandemic in 2020. The objective of this work was to determine the seroprevalence of SARS-CoV-2 antibodies and the level of Knowledge about hand hygiene in medical and nursing interns at the National University of Loja. With a quantitative, prospective, cross-sectional cohort approach, with a population of 137 medical and nursing interns, and a sample of 62, to whom the WHO questionnaire "The Hand Hygiene Knowledge Questionnaire for Health Care Workers ” and immunoassay tests on a blood sample to detect the level of total antibodies . Obtaining that, the seroprevalence of SARS CoV-2 in medical and nursing interns is 12.9% (n=8) seropositive, and 87.1% (n=54) seronegative. Regarding knowledge about hand hygiene, it was evidenced that 58.1% (n=36) showed a medium level of knowledge, 41.9% (n=26) a high level of knowledge, prevalent in women between 20 and 26 years of age in all cases. , which could be explained since it is the group with the largest number of participants. Concluding that of 12.9% (n=8) seropositives, 6.5% (n=4) present a high level of knowledge and 6.5% (n=4) medium knowledge. And of 87.1% (n=54) seronegative, 35.5% (n=22) with a high level of knowledge and 51.6% (n=32) average knowledge, with a p value of 0.88, therefore the alternative hypothesis is adopted. indicating that there is no correlation between the variables